Synthesis and characterization of two-dimensional lead-free (K, Na)NbO3 micro/nano piezoelectric structures - Li-Qian Cheng; Mei Feng; Yiwen Sun; Zhen Zhou; Ze Xu (Journal of Advanced Ceramics, 2020)
Abstract Two-dimensional (2D) lead-free (K, Na)NbO3 (KNN) micro/nano structures with controllable K/Na ratio were successfully fabricated via a two-step molten salt synthesis (MSS). In this work, the reaction factors, including the proportion of molten salts, the types of carbonates, the sintering temperature, and the sintering time, were discussed in detail and the optimized condition was identified. The microstructure of KNN was confirmed by confocal Raman spectroscopy, while piezoresponse force microscopy (PFM) was applied to measure three-dimensional (3D) morphology and piezoelectric properties of KNN particles. The as-synthesized KNN platelets apparently possess anisotropic morphology and uniform structure, the size of which reaches 5–20 µm in length/width and 0.5–1 µm in thickness. It should be noted that the K/Na ratios of the KNN crystals are basically consistent while the proportion of salts changes within a certain range. The enrichment of Na element in the products is also observed, which owes to the smaller ionic radius of Na+ comparing to that of K+. This result provides a reference for the further preparation of textured ceramics and flexible piezoelectric generators.